Examining gendered cassava trait preferences through commercial seed business: a case study of IITA GoSeed and Umudike Seeds in Nigeria - Owoade, D.; Olaosebikan, O.; Bello, A.; Kulakow, P.; Parkes, E.; Olajide, R.; Madu, T.U.; Diebiru-Ojo, E.M.; Okoye, B.; Esiobu, N.S.; Onyeka, J.; Anyim, C.G.; et al. (2025)
This study focuses on how, apart from research, commercial seed initiatives and practices aimed at promoting and selling improved varieties also identified gendered trait preferences of cassava users along the value chain. Since 2015, the public cassava breeding program in Nigeria, led by the International Institute of Tropical Agriculture (IITA) in collaboration with the National Root Crops Research Institute (NRCRI), has carried out various research studies to determine the gendered trait preferences by different cassava users along the whole value chain. These studies inform which crop users the cassava breeding programs target, the traits to select, and the definition of product profiles considering gender. The commercial enterprises IITA GoSeed and Umudike Seeds have engaged cassava seed users who validated the findings of the previous studies. The formal cassava seed system in Nigeria is in a nascent stage. Feedback from this system through seed demand and sales is valuable for breeders. Therefore, this study focused on documenting a case study of how IITA GoSeed and Umudike Seeds commercial initiatives, aimed at promoting and selling improved varieties, identified additional gendered user preferences. A total of six key informant interviews were conducted with IITA GoSeed and Umudike staff. Furthermore, reports and sales data shared by the two companies were assessed. We found that traits such as plant architecture that suppresses weed (branched stems with widespread canopy) and food processing suitability were confirmed as important gendered traits while ratooning ability (allowing to cut stems from an existing plant without the plant being affected much) and sweet taste of tubers which can be eaten boiled without elaborate processing are new gendered traits identified by the two companies. IITA GoSeeds and Umudike Seeds identified that the variety TME419 has the highest sales records among men and women, with more recently released varieties gradually becoming more popular, and their branched soil covering or umbrella shape seems to be an important value-added and gendered trait. Notably, women village seed entrepreneurs (VSEs) showed a distinct preference and demand for the varieties Gamechanger and Farmers' Pride, surpassing the demand recorded among men from both companies. Our findings illustrate that the upcoming commercial seed market demand for different varieties coupled with integrated action research can capture emerging trends among cassava seed and root producers to guide breeding efforts, which is particularly important as breeding is a future investment.